Geospatial analysis and carrying capacity determination for aquaculture development in Phu Quoc island, Viet Nam : - Nguyễn, Thị Hồng Diệp (Asian Institute of Technology School of Engineering and Technology, 2013)
Dissertation research about geospatial analysis and carrying capacity determination for aquaculture development in Phu Quoc island, Viet Nam.